2020
DOI: 10.1101/2020.09.11.20192401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anakinra and Intravenous IgG versus Tocilizumab in the Treatment of COVID-19 Pneumonia

Abstract: Background: COVID-19 can lead to acute respiratory failure and an exaggerated inflammatory response. Studies have suggested promising outcomes using monoclonal antibodies targeting IL-1β (Anakinra) or IL6 (Tocilizumab), however no head to head comparison was done between the two treatments. Herein, we report our experience in treating COVID-19 pneumonia associated with cytokine storm with either subcutaneous Anakinra given concomitantly with intravenous immunoglobulin (IVIG), or intravenous Tocilizumab. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Currently, data are available from seven reports including the multicentre study of Shao et al that explored IVIG immunotherapy in the management of COVID-19 (Table 1). [5][6][7][8][9][10][11] These studies are mostly case series or retrospective, with an exception of one study that was randomised open-label trial. Although retrospective, data from Shao et al included large number of COVID-19 patients compared to other studies, and hence, data are more reliable.…”
Section: Ivig Immunotherapy For the Treatment Of Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, data are available from seven reports including the multicentre study of Shao et al that explored IVIG immunotherapy in the management of COVID-19 (Table 1). [5][6][7][8][9][10][11] These studies are mostly case series or retrospective, with an exception of one study that was randomised open-label trial. Although retrospective, data from Shao et al included large number of COVID-19 patients compared to other studies, and hence, data are more reliable.…”
Section: Ivig Immunotherapy For the Treatment Of Covid-19mentioning
confidence: 99%
“…Another study combined IVIG with anakinra, a recombinant modified IL-1 receptor antagonist. 11 Thus, in view of associated therapies, the therapeutic benefits of IVIG have to be evaluated carefully. It is important to note that studies in autoimmune and inflammatory diseases have reported better outcomes if IVIG is combined with steroids.…”
Section: Ivig Immunotherapy For the Treatment Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The second, a randomized study preprint, was excluded because it compared two experimental therapies (Anakinra/IVIG vs. Tocilizumab) without a control or usual care arm. [ 28 ] Finally, a nonrandomized study that compared early (<48 h) to late (≥48 h) IVIG treatment for COVID-19 was excluded because there was no non-IVIG treatment or usual care arm. [ 26 ] The risk of bias was assessed for each study using the ROBINS-I and GRADE tools.…”
mentioning
confidence: 99%